Crimes against businesses: the wayforward for future research - Hopkins, Matt (The British journal of criminology, 2002)
It has been often been suggested that crimes against business premises have received little attention from criminologists (Gill 1998b; Burrows 1996) However a growing amount of research has emerged in this area and it has indicated that business premises have a higher risk of experiencing crime types such as burglary and criminal damage than households. Despite these findings, there has been little criticism of the methodological approaches employed by the key research and the lack of attention paid to understanding and explaining the crime patterns that emerge from these surveys. This paper reviews the key previous research that has been conducted and begins to consider a number of questions about the future directions for research in this area. First the key research is considered and what this tells us about the nature and extent of victimization against businesses. Second a number of methodological problems with this research are highlighted and finally, consideration is given to potential directions for future research